Binge Drinking Among College Students: A Partial Test of Akers’ Social Structure-Social Learning Theory - Capece, Michael (American journal of criminal justice, 2013)
The present research continues to test the hypothesis from Akers’ Social Structure-Social Learning Theory ( 1998 ) that the effects of structural variables will be mediated by social learning processes. The present research uses Core Alcohol and Drug Survey data from eight diverse college campuses throughout the United States to study binge drinking. This research examines 13 structural features for a full range of college students. The results indicate the social learning variables (rewards, punishments and definitions) mediated most of the structural effects of binge drinking. There were significant interactions, which are not predicted by Akers. The paper discusses the implication of these findings for Akers’ mediation hypothesis.